High‐Resolution Imaging of Fault Zone Structure Along the Creeping Section of the Haiyuan Fault, NE Tibet, From Data Recorded by Dense Seismic Arrays. Issue 9 (10th September 2022) - Zhang, Zhou; Deng, Yangfan; Qiu, Hongrui; Peng, Zhigang; Liu‐Zeng, Jing
Abstract: High‐resolution imaging of fault zone structures is essential for understanding earthquake physics and fault mechanics. As a major left‐lateral strike‐slip fault in northeastern Tibet, fine structures of the damage zone in the creeping (Laohushan) section of the Haiyuan fault remain unclear. To resolve geometry and velocity reduction of the damage zone, we deployed a dense temporary network of 110 seismic stations around the creeping section of the Haiyuan fault. Travel time delays from teleseismic P arrivals suggest an approximately 1‐km‐wide low‐velocity zone, likely illuminating a broader damage zone around the Haiyuan fault. A catalog is constructed for local earthquakes based on phase picks identified from a machine learning technique. The amplification of waveforms from these local events and waveform modeling of fault zone trapped waves indicate a narrower inner damage zone with depth‐dependent width (ranging from 150 to 50 m) that extends to a depth of approximately 4 km. These values are generally consistent with those found on other noncreeping faults in California, suggesting that these damage zone properties are not affected by fault slip behaviors at shallow depth. In addition, a clear bi‐material velocity contrast across the fault is revealed by the analysis of teleseismic P arrivals. Assuming the contrast extends to a depth of 15 km, we find that P‐wave velocity is approximately 5% slower in the crustal block north of the fault. Our study shows that a temporary dense seismic network is effective in illuminating cross‐fault velocity contrast and fault geometry. Plain Language Summary: The Haiyuan fault is a major left‐lateral strike‐slip fault in northeastern Tibet and has hosted two destructive earthquakes (1920 Haiyuan and 1927 Gulang earthquake) in the past century. Along the Laohushan section of the Haiyuan fault, between rupture zones of these two earthquakes, shallow aseismic creep and repeating earthquakes have been detected using geodetic and seismic data. However, the structure of this creeping section is still poorly understood. Therefore, we deployed a dense array with 110 stations crossing the fault surface trace. A catalog with more local earthquakes during the 1‐month recording period is constructed and relocated using this dense array. Based on analyses of signals from nearby and distant earthquakes, we find an approximately 100‐m‐wide slower fault inner zone that can trap incoming seismic energy and a wider (approximately 1‐km wide) low‐velocity damage zone beneath the array. The inferred fault zone structure is consistent with those found along other noncreeping faults in California, suggesting damage zone properties are likely not controlled by fault slip behaviors at shallow depth. The resulting high‐resolution fault zone image also helps improve ground motion prediction and rupture simulation in the Laohushan section of the Haiyuan fault. Key Points: A dense network of 110 seismic stations was deployed around the creeping section of the Haiyuan fault Travel time delays of teleseismic events suggest an approximately 1‐km‐wide low velocity zone around the Haiyuan fault Amplification and waveform modeling of local events infer a flower‐shaped inner damage zone, ranging from 150 to 50 m